2015
DOI: 10.1364/josab.32.001013
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic metamaterial feasible for fabrication with direct laser writing processes

Abstract: Received Month X, XXXX; revised Month X, XXXX; accepted Month X, XXXX;posted Month X, XXXX (Doc. ID XXXXX); published Month X, XXXX Stimulated emission depletion microscopy inspired direct laser writing (STED-DLW) processes can offer diffraction-unlimited fabrication of 3D-structures, not possible with traditional electron-beam or optical lithography. We propose a hyperbolic metamaterial for fabrication with STED-DLW. First, we design meandering wire structures with three different magnetic dipoles which can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 97 publications
(161 reference statements)
0
9
0
Order By: Relevance
“…We have shown that this approach can be used to control the noise amplification while at the same time recover features buried within the noise, thus enabling ultra-high resolution imaging far beyond the previous passive implementations of the plasmon injection scheme [56,88]. The convolution process to construct the auxiliary source in the proposed active scheme may be realized physically by different methods, metasurfaces [74][75][76][77][78][84][85][86] and hyperbolic metamaterials [81][82][83]89] being the primary candidates. A more detailed analysis on the design of such structures to implement the convolved auxiliary source will be the focus of our future research.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that this approach can be used to control the noise amplification while at the same time recover features buried within the noise, thus enabling ultra-high resolution imaging far beyond the previous passive implementations of the plasmon injection scheme [56,88]. The convolution process to construct the auxiliary source in the proposed active scheme may be realized physically by different methods, metasurfaces [74][75][76][77][78][84][85][86] and hyperbolic metamaterials [81][82][83]89] being the primary candidates. A more detailed analysis on the design of such structures to implement the convolved auxiliary source will be the focus of our future research.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] This resolution was extended further by apertureless SNOM systems, which employed a nanoscale scattering probe in the near-field instead of a subwavelength aperture. [7][8][9][10][11][12][13][14] At the turn of the new millennium, imaginative new approaches for controlling electromagnetic waves began to appear for imaging, [15][16][17][18][19][20][21][22][23] photovoltaics, [24][25][26] quantum information processing and simulations, [27][28][29][30][31] wireless communications, 32,33 and novel optical materials, [34][35][36][37][38][39][40] among many others. The advent of metamaterials with simultaneously negative permittivity and permeability 41 brought renewed interest in the properties of left-handed materials first proposed by Veselago,42 which Pendry demonstrated could be applied to sub-diffraction-limited imaging with his "perfect lens."…”
Section: Introductionmentioning
confidence: 99%
“…Also, the imaginary permittivity would preferably be larger at higher frequency. The approach presented here can be also applied to photodetectors and bulk metamaterials 34,[40][41][42] to minimize Ohmic losses.…”
Section: Resultsmentioning
confidence: 99%